Selling Britishness : commodity culture, the Dominions, and empire - Barnes, Felicity (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2022)
"From the 1920s until the outbreak of the Second World War, Australia, Canada, and New Zealand filled British shop windows, newspaper columns, and cinema screens with "British to the core" Canadian apples, "British to the backbone" New Zealand lamb, and "All British" Australian butter. In remarkable yet forgotten advertising campaigns, prime ministers, touring cricketers, "lady demonstrators," and even boxing kangaroos were pressed into service to sell more Dominion produce to British shoppers. But as they sold apples and butter, these campaigns also sold a Dominion-styled British identity. Selling Britishness explores the role of commodity marketing in creating "Britishness." Dominion settlers considered themselves British, and marketed their commodities accordingly. Meanwhile, ambitious Dominion advertising agencies set up shop in London to bring British goods, like Ovaltine, back to the dominions and persuade their own citizens to "Buy British." Conventionally nationalist narratives have posited the growth of independent national identities during the interwar period, though some have suggested enduring imperial sentiment endured. Felicity Barnes takes a new approach, arguing that far from shaking off or relying on any lasting sense of Britishness, Dominion marketing produced it. Selling Britishness further shows that when constructing Britishness, advertisers employed imperial hierarchies of race, class, and gender. Consumption worked to bolster colonialism, and advertising extended imperial power into the everyday. Drawing on extensive new archives, Selling Britishness explores a shared British identity constructed by marketers and advertisers during advertising's golden age."--
The New Empire Marketing: Dominion Organisations in the Metropolis -- Trading on Sentiment? Dominion Campaigns, Emotion and the Cultural Economy of Empire Trade -- 'All-British' Lands: Advertising and the Construction of Commodity Britishness -- 'British to the Core': Trade Films, the Metropolis, and Dominion Identity -- Bringing Another Empire Alive? The Dominions and the Empire Marketing Board -- 'Another Empire Link': Advertising and Britishness in the Dominions.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 15, 2022).
eBooks on EBSCOhost
Keywords: Consumption (Economics) -- Great Britain -- History -- 20th century; Commercial products -- Great Britain -- Marketing -- History -- 20th century; National characteristics, British -- History -- 20th century; Imperialism -- Economic aspects -- Great Britain -- History -- 20th century; Britanniques -- Histoire -- 20e siècle.; Impérialisme -- Aspect économique -- Grande-Bretagne -- Histoire -- 20e siècle.; Société de consommation -- Grande-Bretagne -- Histoire -- 20e siècle.; HISTORY / Modern / 20th Century; Commercial products -- Marketing; Consumption (Economics); Imperialism -- Economic aspects; National characteristics, British; Great Britain; 1900-1999; Australia; Board; Canada; EMB; Ilotts; New Zealand; Publicity; Trade; Walter Thompson; World; advertising; agency; apples; bacon; butter; cinema; co-ethic networks; consumer; consumption; economy; exhibitions; film; food; identity; imperialism; lamb; marketing; press; promotion; racism; settler colonialism; whiteness; History